Online Panoramic Photo Album (OPPA) - Mohamad Suib, Siti Hadijah (Universiti Teknologi Petronas, 2006)
Online Panoramic Photo Album is a system developed for the user who has interest in any related work inpanoramic especially panoramic photographer and developer. Hence, the objective of this system is to integrate panoramic into photo album, to view panoramic images in photo album and study about human perception on panoramic pictures. The scope of study for this project is perform in the university area and collecting feedbacks from various background of user who have readily Information Technology (IT) skills. The author has used Rapid Application Development (RAD) as the methodology to develop the system. The end product will enable the user tonavigate panoramic pictures into photo album, and display multiple panoramic images in one page to show some sortof continuous story telling about the user with the image by enabling comments below the picture. The system also enables the user to arrange the images. As a conclusion, the system being developed to ease the panoramic interest group to navigate and share their works with the rest ofcommunity around the world